The political role of the Arabs in Rome in the second and third centuries AD: Septimius Severus and Philip the Arab as a model - Ahmed Hussein Al Jumaili (مجلة جامعة الأنبار للعلوم الإنسانية, 2023)
Those who is familiar with the ancient history of the Arabs finds a distinct Arab interaction with the Roman Empire from the political and economic aspects. An Arab entity or emirate did not appear without finding a chapter in its history titled Relations with the Roman side, and many historians mention the Roman influence in Arab civilization, or The influence of Roman politics on Arab politics, without mentioning the Arab influence on Roman politics and civilization, and it is known that influence and influence are emitted in parallel and in varying proportions at the same time. Therefore, I preferred to write about the issue of Arab influence in the Roman Empire, specifically on the political side, and to give a model for personalities of Arab origins who ruled the Roman Empire, and they are: (Septimius Severus) and (Philippe the Arab). And all the Arab emperors who ruled Rome are from the Severian dynasty, whose emperors are divided into two parts: the first is the African section, and they are Sever and his sons, the second part is Al-Ghabal and Alexander, and they belong to the Arabs of Syria